Peran Dinas Kebudayaan Dan Pariwisata Dalam Upaya Pelestarian Tarian Adat Suku-Suku - Fransiskus Wuniyu; Welem Levi Betaubun (Musamus Journal of Public Administration, 2019)
The government Program that has been proclaimed is by sending participants of Pesparawi and festival of Papua creations that are always carried out every year in Papua province. However, with the program's two major activities, it has not been able to preserve the culture of these tribes which increasingly disappear with the inclusion of modern culture. The purpose of writing is to know the role of the Culture and Tourism office in the preservation efforts of the traditional dance of the tribes in Mappi County region. Methods of using qualitative. The results showed the role of the Culture and Tourism service has never involved the community, group of workshops, LMA and cultural observers in the participation to advise the development of traditional dances (art and Culture Mappi). The role of the Culture and Tourism department in preserving indigenous dances, many programs are being conducted, but only a few are carried out. Programs that have not been implemented are due to lack of cost/budget and execution time. For the preservation process, restoration and revitalization of the role of culture and tourism with LMA, Mayarakat, group of workshops and other elements that are concerned about indigenous dances of these indigenous tribes have not been or are intertwined.